Analisa Kemampuan Kaligrafi Mahasiswa Jurusan Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sumatera Utara - Khairani, Beby; Ichsan, Sayed Muhammad (Alhamra Jurnal Studi Islam, 2023)
The problem that often occurs in students majoring in Arabic Language Education is that they often experience difficulties and errors in writing the correct Arabic letters, this occurs due to their lack of ability to master these basic techniques. Calligraphy is beautiful writing that is made according to predetermined rules, one of which is writing letters that can be connected. These rules can be used as support for learning Arabic. This study aims to analyze how the calligraphy skills of students majoring in Arabic Language Education, at the Faculty of Tarbiyah, and Teaching Sciences at the State Islamic University of North Sumatra. The method used in this research is descriptive using a qualitative approach. The data collection technique used was by conducting interviews and collecting references from other literature related to the research. The results of this study indicate that there are students who have skills in calligraphy have fewer comparisons than students who do not have the ability or even interest in calligraphy because they do not master the aspects that form the basis of the art of calligraphy. This study also shows that there is a relationship between interest and calligraphy skills possessed by students, this is shown by the factors that influence interest in learning such as facilities, infrastructure, and facilities.